Analysis of Conversational Implicature Found in the Silence of the Lambs Movie - Anggi Lastri Pinayungan; Lastri Wahyuni Manurung; Carolina Pakpahan (Universitas Cokroaminoto Palopo, 2024)
This research employs a descriptive qualitative approach to examine Conversational Implicatures found in